Development of an Instrument for Measuring Learner–Teacher Transactional Distance. Issue 2 (2nd April 2016) - Giossos, Yiannis; Koutsouba, Maria; Mavroidis, Ilias
ABSTRACT: An instrument was developed to assess the perceived learner–teacher transactional distance in the context of the Hellenic Open University and to provide psychometric evidence of reliability and validity of the interpretation of the scores derived from the scale. First, an elicitation study gathered information on students' beliefs and feelings about their teachers' behavior. Two dimensions of learner–teacher transactional distance, namely, co-understanding and awareness, were revealed. Then, an item pool was developed and the preliminary questionnaires (one for each dimension) were field tested on 60 postgraduate students who commented on their clarity. Reliability and validity were then tested using exploratory and confirmatory factor analysis with two samples of 220 and 201 postgraduate students. The confirmatory factor analysis results indicated good model fit for the dimensions of co-understanding and awareness. Univariate F tests showed no significant difference between males and females for (a) co-understanding of cognitive skills and aptitudes, (b) co-understanding of emotional state, (c) awareness of cognitive skills and aptitudes, and (d) awareness of emotional state. A final questionnaire included ten items for the co-understanding dimension and fifteen items for the awareness dimension.